Framing Analysis of Media Coverage of Papuan Riots on SKH Kompas and Tirto.id in 2019 - Triwardani, M.A, Reny; Karolus, Meike Lusye; Sosiawan, Edwi Arief (Jurnal Ilmu Komunikasi, 2024)
The study examines the media's framing of the Papuan riots, with a focus on protests against racial discrimination. It highlights how stereotypes like "lazy" and "separatist" exacerbate social tensions for Papuans, particularly in urban areas. Triggered by a racially charged incident in Surabaya, these riots led to significant protests in Papua and West Papua, receiving national media coverage. Through qualitative analysis of news from SKH Kompas and Tirto.id, the research shows selective framing, often emphasizing violence and commodifying racial tensions, which perpetuates discrimination. The study advocates for the reevaluation of media narratives to improve the representation of marginalized groups and promote dialogue and reconciliation.